2022
DOI: 10.1128/mbio.01476-22
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Cellodextrin and Glucose Uptake in Clostridium thermocellum

Abstract: Highly efficient sugar uptake is important to microbial cell factories, and sugar transporters are therefore of great interest in the study of industrially relevant microorganisms. Clostridium thermocellum is a lignocellulolytic bacterium known for its multienzyme complex, the cellulosome, which is of great potential value in lignocellulose biorefinery. In this study, we clarify the function and mechanism of substrate specificity of the five reported putative sugar transporters using ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 77 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…The past decade has shown that many thermophiles of biotechnological importance possess multiple CUT1 and CUT2 ABC transporters for monosaccharide and oligosaccharide uptake: Thermus thermophilus, Thermotoga maritima, Pyrococcus furiosus, Caldicellulosiruptor saccharolyticus, Anaerocellum bescii (D. A. Rodionov et al., 2013 ), (VanFossen et al., 2009 ; Stincone et al., 2015 ), (D. A. Rodionov et al., 2021 ), (Chandravanshi et al., 2019 ). The ABC cellodextrin and glucose transporters in C. thermocellum have also garnered significant attention (Nataf et al., 2009 ; Yan et al., 2022 ). Between both CUT1 and CUT2 ABC transporters, thermophiles are well-equipped to uptake the diverse array of sugars in their native environments, which tend to be limiting in growth substrate (Koning et al., 2002 ; Bosdriesz et al., 2015 ).…”
Section: Sugar Transport In Thermophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The past decade has shown that many thermophiles of biotechnological importance possess multiple CUT1 and CUT2 ABC transporters for monosaccharide and oligosaccharide uptake: Thermus thermophilus, Thermotoga maritima, Pyrococcus furiosus, Caldicellulosiruptor saccharolyticus, Anaerocellum bescii (D. A. Rodionov et al., 2013 ), (VanFossen et al., 2009 ; Stincone et al., 2015 ), (D. A. Rodionov et al., 2021 ), (Chandravanshi et al., 2019 ). The ABC cellodextrin and glucose transporters in C. thermocellum have also garnered significant attention (Nataf et al., 2009 ; Yan et al., 2022 ). Between both CUT1 and CUT2 ABC transporters, thermophiles are well-equipped to uptake the diverse array of sugars in their native environments, which tend to be limiting in growth substrate (Koning et al., 2002 ; Bosdriesz et al., 2015 ).…”
Section: Sugar Transport In Thermophilesmentioning
confidence: 99%
“…Beyond maltodextrin-binding proteins, a recent study by Yan et al. ( 2022 ) has revealed new structural and biophysical insights into cellodextrin transport in C. thermocellum (Yan et al., 2022 ). Five ABC sugar transporters—A, B, C, D, L—collectively mediate cellodextrin and laminaribiose uptake (Nataf et al., 2009 ; F. Yan et al., 2022 ).…”
Section: Substrate-binding Proteins Determine Abc Transporter Specifi...mentioning
confidence: 99%
“…The combination of ABC transport protein and cellobiose phosphorylase is a common strategy concerning cellobiose transportation in R. thermocellum (Parisutham et al, 2017). Five putative cellodextrin-specific ABC transporters, labeled as CbpA-D and Lbp, had identified in R. thermocellum DSM 1313 (Nataf et al, 2009); Yan et al found that only CbpB plays a key role in cellobiose transport using the functional verification of CbpA-D by genetic inactivation (Yan et al, 2022). We identified four ABC sugar transporters that specifically transport polysaccharides by gene annotation and conserved domain database analysis, but the high affinity for binding to cellobiose needs further proof in future works.…”
Section: Genome Specificity Of Cellobiose Hydrolysis By Ruminiclostri...mentioning
confidence: 99%
“…Cellobiose is the major product released by the cellulolytic system of the model cellulolytic bacterium Ruminiclostridium cellulolyticum [5]. It is imported, along with other and have to be taken up by cellulolytic organisms to sustain their growth [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of many anaerobic cellulolytic clostridia, cellulases and related enzymes necessary for the degradation of other plant cell wall polysaccharides are gathered in multi-enzymatic complexes called cellulosomes [ 1 ]. During the hydrolysis of cellulose, soluble cellodextrins ranging from two (cellobiose) to six (cellohexaose) glucose units are released and have to be taken up by cellulolytic organisms to sustain their growth [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%